Does supplier evaluation impact process improvement? - Shiva H C Prasad; Giridhar B Kamath; Gopalkrishna Barkur; Rakesh Naik (Journal of Industrial Engineering and Management, 2016)
– Purpose: The research explores and examines factors for supplier evaluation and its impact on process improvement particularly aiming on a steel pipe manufacturing firm in Gujarat, India. Design/Methodology/approach: The conceptual research framework was developed and hypotheses were stated considering the analysis of literature and discussions with the managers and engineers of a steel pipe manufacturing company in Gujarat, India. Data was collected using in-depth interview. The questionnaire primarily involves the perception of evaluation of supplier. Factors influencing supplier evaluation and its influence on process improvement is also examined in this study. The model testing and validation was done using partial least square method. Outcomes signified that the factors that influence evaluation of the supplier are quality, cost, delivery and supplier relationship management. Findings: The study depicted that quality and cost factors for supplier evaluation are insignificant. The delivery and supplier relationship management have significant influence on evaluation of the supplier. The research also depicted that supplier evaluation has significant influence on process improvement. Research limitations/implications: The study has been made specifically for ABC steel pipe manufacturing industry in Gujarat, India and may not be appropriate to the other industries or any parts of the world. There is a possibility of response bias as the conclusions of this research was interpreted on survey responses taken from the employees of case study company, so it is suggested that future research can overcome this problem by employing various methodologies in addition to surveys like carrying out focus group and in-depth interviews, brainstorming sessions with the experts etc. Originality/value: Many researchers have considered quality, cost and delivery as the factors for evaluating the suppliers. But for a company it is quintessential to have good relationship with the supplier. Hence, the factor, supplier relationship management is considered for the study. Also, the case study company focused more on quality and cost factors for the supplier evaluation of the firm. However, delivery and supplier relationship management are also equally important for a firm in evaluating the supplier.
Keywords: 330; cost; partial least square; supplier relationship management; delivery; process improvement; quality; supplier evaluation